2019
DOI: 10.3389/fmars.2019.00200
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Conservation Features and Species Associated With Subsea Pipelines: Considerations for Decommissioning

Abstract: Oil and gas pipelines that lie exposed on the seabed can function as "artificial reefs," providing habitat for fish and benthic species, including some that are listed under conservation designations. As the offshore hydrocarbon industry matures, operators and national governments must decide whether decommissioned pipelines should be left in situ or removed for onshore disposal. In most jurisdictions, there is a requirement to evaluate the environmental consequences of different pipeline decommissioning optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Access to these data for scientific study can provide insights into the longer-term effects of industry activity (Henry et al, 2017) but are often inaccessible because they are presented as commercial consultancy reports. Opportunistic studies of seafloor infrastructure like this, and similar observations associated with industry structures such as well heads (Pradella et al, 2014) and pipelines (McLean et al, 2017) have revealed insights into how fishes and invertebrates utilize these structures, including the presence of species and features of conservation importance (Rouse et al, 2019). They provide much needed data to understand the role of these structures in the ecology of poorly studied habitats and inform environmental decision making on all stages of industry from exploration to decommissioning.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Access to these data for scientific study can provide insights into the longer-term effects of industry activity (Henry et al, 2017) but are often inaccessible because they are presented as commercial consultancy reports. Opportunistic studies of seafloor infrastructure like this, and similar observations associated with industry structures such as well heads (Pradella et al, 2014) and pipelines (McLean et al, 2017) have revealed insights into how fishes and invertebrates utilize these structures, including the presence of species and features of conservation importance (Rouse et al, 2019). They provide much needed data to understand the role of these structures in the ecology of poorly studied habitats and inform environmental decision making on all stages of industry from exploration to decommissioning.…”
Section: Discussionmentioning
confidence: 87%
“…Actinauge richardi was the most abundant of the larger epifaunal species on Structure A and is common on offshore infrastructure in the North Sea (Rouse et al, 2019) and on a variety of substratum west of Shetland (Jones and Gates, 2010). Filograna implexa was present on the panels of Structure A, but colonies were largest and most abundant on the inner column of the structure, away from potential disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have raised the potential advantages and limitations of using repurposed structural surveys (e.g., [14][15][16]. As one study noted [16] "Most ROV operations are conducted by industry in a way that fulfills immediate industry requirements but which can confound scientific interpretations of the data.…”
Section: Plos Onementioning
confidence: 99%
“…However, there also exists oil and gas ROV engineering surveys of platforms and associated infrastructure (i.e., pipelines, subsea equipment and wellheads) conducted as part of routine physical integrity inspections. In the past few years, researchers off western Australia [8][9][10][11][12] and in the North Sea [13,14] have begun to use this archival footage to characterize the biological communities associated with the offshore oil and gas structures.…”
Section: Introductionmentioning
confidence: 99%